Pemberdayaan Masyarakat Pesisir Berbasis Model Asset based Community Development di Kecamatan Rupat Utara - Rina Susanti; Yoskar Kadarisman; Nur Hijaya Hening; Alika Kumala Siregar (LP2M INSURI Ponorogo, 2025)
This community service initiative aims to strengthen the independence of coastal communities by optimizing local assets through the Asset-Based Community Development approach in Puteri Sembilan Village, North Rupat District, Bengkalis Regency, which has a mangrove forest potential of 307 hectares. The program aims to enhance the skills and interest of the community in sustainably managing mangrove resources. Through the participatory method, activities are carried out in four main stages: identification, asset mapping, capacity building, and collaborative training involving Raja Sofia MSME women's groups, Coastal Conservation Groups, and Fishermen's Groups. The focus of the program lies on the use of the Kedabu fruit (Sonneratia Ovata) as a product of mangrove forests to produce innovative food products with economic value. The results of the activity showed a significant increase in aspects of knowledge, ecological awareness, and community entrepreneurial motivation. Innovative products have been successfully developed, including dodol, syrup, and jams made from papabu fruit. Evaluation of service activity achievement is conducted through pretests using closed-ended questionnaire instruments. As a result, among 20 participants, there was a 55% increase in knowledge and interest in processing mangrove forest products. The findings confirm that the ABCD model is effective in building local capacity, increasing ecological awareness, and promoting the sustainable economic transformation of coastal communities based on their natural potential. The sustainability of the program demands cross-stakeholder collaboration on the village development agenda to ensure long-term impact.